Global trends in incidence and death of neonatal disorders and its specific causes in 204 countries/territories during 1990-2019 - Zejin Ou; Danfeng Yu; Yuanhao Liang; Huan He; Wenqiao He; Yongzhi Li; Minyi Zhang; Yuhan Gao; Fei Wu; Qing Chen (BMC, 2022)
Abstract Background Neonatal disorders (ND) are a significant global health issue. This article aimed to track the global trends of neonatal disorders in 204 countries/territories from 1990 to 2019. Methods Data was explored from the Global Burden of Disease study 2019. Estimated annual percentage change (EAPC) and age-standardized rate (ASR) were calculated to quantify the trends of neonatal disorders and their specific causes, mainly included neonatal preterm birth (NPB), neonatal encephalopathy due to birth asphyxia and trauma (NE), neonatal sepsis and other neonatal infections (NS), and hemolytic disease and other neonatal jaundice (HD). Results In 2019, there were 23,532.23 × 103 incident cases of ND, and caused 1882.44 × 103 death worldwide. During 1990-2019, trends in the overall age-standardized incidence rate (ASIR) of ND was relatively stable, but that of age-standardized death rate (ASDR) declined (EAPC = -1.51, 95% confidence interval [CI]: -1.66 to -1.36). Meanwhile, decreasing trends of ASDR were observed in most regions and countries, particularly Cook Islands and Estonia, in which the respective EAPCs were -9.04 (95%CI: -9.69 to -8.38) and -8.12 (95%CI: -8.46 to -7.77). Among the specific four causes, only the NPB showed decreasing trends in the ASIR globally (EAPC = -0.19, 95%CI: -0.26 to -0.11). Decreasing trends of ASDR caused by ND underlying specific causes were observed in most regions, particularly the HD in Armenia, with the EAPC was -13.08 (95%CI: -14.04 to -12.11). Conclusions Decreasing trends of death caused by neonatal disorders were observed worldwide from 1990 to 2019. However, the burden of neonatal disorders is still a considerable challenge, especially in low-resource settings, which need more effective health strategies.